The logarithmic equation f(x) = log(100) in the form g(x) = k + a log b(r – h) is f(x) = 0 + 2log(10 - 0)
The equation is given as:
f(x) = log(100)
Express 100 as 10^2
f(x) = log(10^2)
Apply the law of logarithm
f(x) = 2log(10)
Subtract 0 from 10
f(x) = 2log(10 - 0)
Add 0 to the equation
f(x) = 0 + 2log(10 - 0)
Hence, the logarithmic equation f(x) = log(100) in the form g(x) = k + a log b(r – h) is f(x) = 0 + 2log(10 - 0)
Read more about logarithmic equation at:
https://brainly.com/question/13473114
#SPJ1